2011
DOI: 10.1016/j.canlet.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule antagonists for CXCR2 and CXCR1 inhibit human colon cancer liver metastases

Abstract: CXCR1 and CXCR2 are G-protein coupled receptors, that have been shown to play important role in tumor growth and metastasis, and are prime targets for the development of novel therapeutics. Here, we report that targeting CXCR2 and CXCR1 activity using orally active small molecule antagonist (SCH-527123, SCH-479833) inhibits human colon cancer liver metastasis mediated by decreased neovascularization and enhanced malignant cell apoptosis. There were no differences in primary tumor growth. These studies demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 38 publications
(44 reference statements)
3
79
0
Order By: Relevance
“…A recent study has shown the potential of SCH-527123 in inhibiting human colon liver metastases using in vivo models (18). In our in vitro study, we showed that SCH-527123 treatment inhibited cell proliferation and induced apoptosis in both HCT116 and Caco2 parental and IL-8-overexpressing colorectal cancer cells.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…A recent study has shown the potential of SCH-527123 in inhibiting human colon liver metastases using in vivo models (18). In our in vitro study, we showed that SCH-527123 treatment inhibited cell proliferation and induced apoptosis in both HCT116 and Caco2 parental and IL-8-overexpressing colorectal cancer cells.…”
Section: Discussionsupporting
confidence: 56%
“…SCH-527123, as a novel and selective antagonist of the CXCR2, has shown efficacy in the treatment of inflammatory diseases (17). Moreover, Singh and colleagues showed that SCH-527123 treatment inhibited human melanoma cancer growth and colorectal cancer liver metastases by decreasing tumor cell proliferation, angiogenesis, and enhancing the apoptosis of malignant cells (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, multiple small molecule inhibitors of the most important chemokine receptors, CXCR1 and CXCR2, have been generated. A few of these inhibitors showed efficacy in the treatment of experimental cancers (Bolitho et al 2010;Tazzyman et al 2011;Varney et al 2011). In this study, we determined the effects of our newly synthesized CXCR1/2 inhibitor G31P in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies gave evidence that blocking CXCR1 and especially CXCR2 signaling, either by use of neutralizing antibodies or small-molecule inhibitors, inhibits colon cancer metastasis to liver (31,32). One earlier study showed similar results for a CXCR1/ CXCR2 blockade on lung metastasis development in a renal cell carcinoma model (33).…”
Section: Discussionmentioning
confidence: 90%